KINERJA PELAYANAN ADMINISTRATIF MASYARAKAT KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN 2016 - Septyani, Ericha Tri; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One of purpose to make division of distric is to improve public administration services for people with responsive, accountable, and effisient. But, based on interview result with Mr. Rahmad as elder of Tanjung Village on July, 12 2017, public administration services in Koto Kampar Hulu district Kampar regency not fully run facile because the process is still takes a long time. Formulation of the problem: how is Performance Of Public Administrative Services In Koto Kampar Hulu District Kampar Regency in 2016? What factors that inhabiting Performance Of Public Administrative Services In Koto Kampar Hulu District Kampar Regency in 2016? Research purpose: To known Performance Of Public Administrative Services In Koto Kampar Hulu District Kampar Regency in 2016, To known What factors that inhabiting Performance Of Public Administrative Services In Koto Kampar Hulu District Kampar Regency in 2016. Data obtained is analyzed by descriptive-qualitative. Dimension SERVQUAL in public administration services Koto Kampar Hulu district Kampar Regency 2016. The tangibles is goverment services, community services, development services. Reabilty, durability reability performance of administration is not yet maximal. Responsiveness, information of requitmen to be complicated to get administration service need to see the sticky information. Assurance, is administration service implementers already have knowledge and abilities about system, mechanism, and procedure. Emphaty is after get complaint, advice, and input so Camat doing internal controlling to check the truth of complaint, advice, and input then will be evaluated performance administration implementer for improvment. The factors that inhabiting: some time, there is no administration service implementer, adminisration service completation is take many time, there is empty posiion, lack of number administration services computer operators, electricity is often extinguished, and there is no internet network. Keyword: Services, Performance, and Administrative